Anatomical and Physiological Changes and Hygienic Status in the Oral Cavity of Patients Using Fixed Implant-Supported Dentures (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Fixed implant-supported dentures have revolutionized modern dentistry by providing stable, aesthetic, and functional rehabilitation for patients with missing teeth. However, their long-term use induces significant anatomical and physiological changes in the oral cavity. The presence of implants affects the surrounding bone tissue, mucosa, and salivary glands. Over time, adaptive remodeling occurs in the alveolar bone, while the mucosal tissues undergo modifications in thickness, keratinization, and sensitivity. Moreover, the altered mechanical load distribution may influence blood circulation and tissue metabolism around the implant sites.